Hetero-site cobalt catalysts for higher alcohols synthesis by CO2 hydrogenation: A review. (January 2023) - Liu, Shuilian; He, Yiming; Fu, Weijie; Chen, Jian; Ren, Jie; Liao, Longfei; Sun, Ruiyan; Tang, Zhenchen; Mebrahtu, Chalachew; Zeng, Feng
Abstract: Synthesis of higher alcohols by CO2 hydrogenation is a promising way to mitigate CO2 emissions, meanwhile producing value-added fuels and chemicals. However, CO2 hydrogenation to higher alcohols is kinetically hindered and due to the absence of highly efficient catalysts, its industrial implementation is still limited. Among the catalysts designed for this reaction, Co-based catalysts are widely investigated due to earth-abundance and economic, possessing also relatively high activity and selectivity for this reaction. Considering the nature of the active site, the hetero sites of Co-based catalysts such as Co 0 -CoO, Co 0 -Co δ+, and Co2 C-NaCo2 C are critical for higher alcohol synthesis by CO2 hydrogenation. Thus, in this review, we first introduce the roles of Co 0, CoO, Co δ+, and Co2 C, as well as strategies to tailor their structure which influences the performance in CO2 hydrogenation. Then, we discuss the strategies to create highly efficient hetero-site Co-based catalysts. Finally, emerging methodologies yet to be explored and future directions to achieve highly efficient hetero-site Co catalysts for CO2 hydrogenation to higher alcohols are discussed. Graphical Abstract: ga1 Highlights: Catalytic activity of Co 0, CoO, Co2 C, and Co δ+ sites for CO2 hydrogenation is discussed. Strategies for creating hetero Co sites to enhance higher alcohol synthesis are discussed. Strategies to further promote higher alcohol formation over Co-based catalysts are proposed.